Fenomena Keracunan Makanan Bergizi Gratis (MBG) Pada Siswa Sekolah Dalam Perspektif Muhammad Abduh : Penelitian - Fitriah; Iqbal Maulana; Lulu Nurul Khasanah; Andi Rosa (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The phenomenon of poisoning in the Free Nutritious Food (MBG) program experienced by a number of school students in Indonesia has caused a critical discourse on educational governance, public health, and social ethics in the implementation of government programs. This poisoning incident that should not have occurred is an indicator of weaknesses in the surveillance system, policy implementation, and quality of food provided. To delve into this issue, the perspective of the renewal of Islamic thought from Muhammad Abduh can provide a relevant framework of analysis, especially related to moral responsibility, rationality, and social reform. Abduh, as an Islamic modernist figure, emphasized the importance of the use of common sense (al-'aql), social ethics, and educational reform as the foundation for the formation of a civilized society. In the context of the phenomenon of MBG poisoning, Abduh's thinking demands an integration between rationality and moral values in every public policy. He argued that the ummah and the government should not be trapped in a formalistic work pattern without ensuring substantive benefits for society. MBG programs, while well-intentioned to improve students' nutritional status and learning readiness, become counterproductive when the procurement, distribution, and oversight processes are not based on science, transparency, and accountability. Abduh emphasized that every policy must be based on the principles of maslahah (community welfare) and amanah (accountability), so that potential dangers such as poisoning must be anticipated through careful planning and scientific supervision. Abduh's thinking also assesses that education is not limited to academic aspects, but includes the formation of a healthy and safe social environment.